Health benefits of organic food: effects of the environment - Givens, I.; Baxter, S.; Baxter, S.; Givens, I.; Minihane, A. M.; Minihane, A. M.; Shaw, E.; Shaw, E. (Wallingford :CABI, 2008)
This book is the result of a Workshop. The objective of this Workshop was to address three key issues: the quantifiable effects of organic in comparison with conventionally produced food on human health; the environment impact on these possible health benefits; and how the public perceives these benefits. To address these issues, the Workshop examined such factors as the role of certain nutrients (e.g. nitrate and long-chain n-3 polyunsaturated fatty acids acids) in the prevention and promotion of chronic disease, the potential health benefits of bioactive compounds in plants (e.g. flavonoids), the prevalence of food-borne pesticides and pathogens and how both local and global environmental factors may affect any differences between organic and conventionally produced foods.
Keywords: EE720 - Consumer Economics; HH430 - Pesticide and Drug Residues and Ecotoxicology, (New March 2000); QQ200 - Food Contamination, Residues and Toxicology; QQ500 - Food Composition and Quality; VV100 - Human Nutrition (General); VV500 - Human Health and the Environment